Hollywood drive : what it takes to break in, hang in & make it in the entertainment industry - Honthaner, Eve Light, 1950- (Routledge, 2018)
"Hollywood Drive explores the realities of the industry: various career options, effective job search strategies, how to write an effective cover letter and resume, what to expect on your first job, the significance of networking and building solid industry relationships, how a project is sold, and how a production office and set operate. You'll learn how to define your goals and make a plan to achieve them, how to survive the tough times, how to deal with big egos and bad tempers, and how to put your passion to work for you. Although no book or class can totally prepare you for a career in the entertainment industry, Hollywood Drive offers insights, direction, and a sense of confidence."--Publisher's description